2006
DOI: 10.4049/jimmunol.177.10.7346
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tolerance to Innocuous Inhaled Antigen Relies on a CCR7-Dependent Dendritic Cell-Mediated Antigen Transport to the Bronchial Lymph Node

Abstract: Allergic airway diseases such as asthma are caused by a failure of the immune system to induce tolerance against environmental Ags. The underlying molecular and cellular mechanisms that initiate tolerance are only partly understood. In this study, we demonstrated that a CCR7-dependent migration of both CD103+ and CD103− lung dendritic cells (DC) to the bronchial lymph node (brLN) is indispensable for this process. Although inhaled Ag is amply present in the brLN of CCR7-deficient mice, T cells cannot be toleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(191 citation statements)
references
References 39 publications
12
177
1
1
Order By: Relevance
“…Yen et al 26 reported that DCs matured within inflammatory sites require both chemokine receptor type 7 and prostaglandin E2-induced MMP9 for directional migration to draining lymph nodes. Hintzen et al 27 reported that continuous DC-mediated transport of inhaled antigen to the bronchial lymph node is critical for the induction of tolerance to innocuous antigens. The roles of MMP9 are not restricted to DC migration.…”
Section: Discussionmentioning
confidence: 99%
“…Yen et al 26 reported that DCs matured within inflammatory sites require both chemokine receptor type 7 and prostaglandin E2-induced MMP9 for directional migration to draining lymph nodes. Hintzen et al 27 reported that continuous DC-mediated transport of inhaled antigen to the bronchial lymph node is critical for the induction of tolerance to innocuous antigens. The roles of MMP9 are not restricted to DC migration.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators could show that tolerance induction and formation of Treg depends on an intact pDC system [9,36,37]. Others found that tolerance also required cDC that migrated to the MLN in a CCR7-dependent manner [38,39]. In some models of inhalation tolerance, CD103 1 CD11b À cDC were better at cross-tolerizing the CD8 1 lymphocytes, whereas CD11b hi cDC tolerized CD4 1 T cells.…”
Section: Antigen Presentation and T-cell Polarizationmentioning
confidence: 99%
“…For continuous BrdU incorporation, mice were injected initially with 3 mg of BrdU in 200 l of PBS and subsequently received BrdU via the drinking water (80 mg of BrdU in 100 ml of water). Induction of allergic Ag-specific reactions in the lung and intestine by sensitization/challenge with OVA has been described previously (14,15). Ag challenge was performed either as dried OVA aerosol (1% OVA in water for 20 min/day) for 7 consecutive days or orally every second day (50 mg of OVA in PBS by gavage) for five to six times.…”
Section: Micementioning
confidence: 99%